Digital gait measures, but not the 400-meter walk time, detect abnormal gait characteristics in people with Prediabetes - Shah, Vrutangkumar V.; Carlson-Kuhta, Patricia; Mancini, Martina; Sowalsky, Kristen; Horak, Fay B. (Gait & posture, 2024)
Abnormal gait characteristics have been observed in people with diabetic neuropathy, but it is unclear if subtle changes in gait occur in prediabetic people with impaired fasting glucose (IFG). The aims of this study were: (1) to investigate if digital gait measures discriminate people with prediabetes from healthy control participants (HC) and (2) to investigate the relationship between gait measures and clinical scores (concurrent validity). 108 people with prediabetes (71.20 ± 5.11 years) and 63 HC subjects (70.40 ± 6.25 years) wore 6 inertial sensors (Opals by APDM, Clario) while performing the 400-meter fast walk test. Fifty-five measures across 5 domains of gait (Lower Body, Upper Body, Turning, and Variability) were averaged. Analysis of Covariance was used to investigate the group differences, with body mass index as a covariate. Pearson’s correlation coefficient assessed the association between the gait measures and the Short Physical Performance Battery (SPPB) score. Nine gait measures were significantly different (p < 10–4) between IFG and HC groups. Step duration, cadence, and turn velocity were the most discriminative measures. In contrast, traditional stop-watch time was not significantly different between groups (p = 0.13), after controlling for BMI. Cadence (r = −0.37, p < 0.001), step duration (r = −0.39, p < 0.001), and turn velocity (r = 0.47, p < 0.001) showed a significant correlation with the SPPB score. Body-worn inertial sensors detected gait impairments in people with prediabetes that related to clinical balance test performance, even when the traditional stop-watch time was not prolonged for the 400-meter walk test. •108 people with prediabeties and 63 healthy subjects participated in this study.•Objective gait measures from 400-meter walk test were compared between groups.•Step duration, cadence, and turn velocity were the most discriminative measures.•Traditional stop-watch time from 400-meter walk test was not different between groups.•Digital gait measures show a potential to be used in prediabetic clinical trials.